2011
DOI: 10.1111/j.1365-2648.2011.05650.x
|View full text |Cite
|
Sign up to set email alerts
|

The discursive practices of nurse practitioner legislation in Australia

Abstract: This paper exposes the influence that powerful discourses can have on a major change to professional practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…To date there are approximately 700 practicing NPs in Australia (Harvey, Driscoll, & Keyzer, 2011), a small number compared to the 150,000 NPs in the United States (Rosenberg, 2012). Resistance to the NP role by medical practitioners is suggested as one of the key reasons for this small number.…”
Section: Introductionmentioning
confidence: 99%
“…To date there are approximately 700 practicing NPs in Australia (Harvey, Driscoll, & Keyzer, 2011), a small number compared to the 150,000 NPs in the United States (Rosenberg, 2012). Resistance to the NP role by medical practitioners is suggested as one of the key reasons for this small number.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, they were saddened by the loss of potential for nursing and society because of this regulatory culture. Although there is very little empirical research on this topic, a few studies, as mentioned earlier, corroborate these findings about how nurses who are working in innovative and advanced roles struggle with regulatory barriers (Donald et al., ; Harvey et al., ; Sangster‐Gormley et al., ; Wall, ). As Sandelowski () asserts, the summaries that are derived through qualitative description research are valuable as end products on their own but also serve as entry points for further study.…”
Section: Discussionmentioning
confidence: 83%
“…To date, there has been little investigation of the impacts and consequences of existing professional regulatory practices on nurses and nursing (Benton, Gonzalez‐Jurado, & Beneit‐Montesinos, ). Research by Harvey, Driscoll, and Keyzer () and literature reviews conducted by Sangster‐Gormley, Martin‐Misener, Downe‐Wamboldt, and DiCenso () and Donald et al. () revealed that regulatory processes have been a constraining factor in the implementation of the nurse practitioner (NP) role, an innovative, advanced nursing role.…”
Section: Background: Nursing Roles and Regulationmentioning
confidence: 99%
“…As such, nurse practitioner roles have typically been implemented as either substitutes for medical professionals or as complementing and enhancing the overall care provided by medical professionals (Bonsall and Cheater 2008). In contrast to a biomedical focus of diagnosis and disease treatment held by many medical professionals, nurse practitioners practice within a holistic philosophy of care that emphasises therapeutic relationships and awareness of the whole person (Gould, Johnstone et al 2007, Harvey, Driscoll et al 2011). …”
Section: Introductionmentioning
confidence: 99%